Regulating the sex trade: a comparative study between the legal policies adopted in selected countries - Jenita Kanapathy (Penerbit Universiti Kebangsaan Malaysia, 2020)
The term the “oldest profession in the world” often refers to prostitution which had withstood the test of time and thrives in different social orders and societies around the world since antiquity. However, the laws and regulations overseeing this trade will in general vary from nation to nation. In a few nations, the sex trade has been legitimised while in others, it has been criminalised and even decriminalised. Also, there are nations around the world that adopted unregulated policies with respect to the sex trade. This paper distinguishes the kind of legitimate strategies existing around the world in terms of managing the sex trade and analyses the approaches that are adopted by selected nations; which are India, Singapore, Hong Kong and Turkey. Based on the legal framework in the selected countries, the paper recommends conceptual approaches to be undertaken as an alternative to outright criminalisation of the sex trade.